Stable, Surfactant‐Free Graphene–Styrene Methylmethacrylate Composite for Ultrafast Lasers. Issue 7 (1st April 2016) - Torrisi, Felice; Popa, Daniel; Milana, Silvia; Jiang, Zhe; Hasan, Tawfique; Lidorikis, Elefterios; Ferrari, Andrea C.
Abstract : Graphene–polymer composites play an increasing role in photonic and optoelectronic applications, from ultrafast pulse generation to solar cells. The fabrication of an optical quality surfactant‐free graphene‐styrene methyl methacrylate composite, stable to large humidity and temperature ranges is reported. The composite is tailored for photonic applications showing wavelength‐independent linear absorption in the visible and near‐infrared. When tested in a mode‐locked laser, it allows the generation of stable ≈326 fs mode‐locked pulses at 1550 nm, unperturbed by environmental conditions. The composite continues to operate as a saturable absorber even under complete water immersion at 60 °C. This confirms its stability against high‐temperature and humidity. Abstract : A surfactant‐free graphene–styrene methyl methacrylate composite, stable to large humidity and temperature ranges is designed for photonic applications. The composite shows wavelength‐independent linear absorption in the visible and near‐infrared. When tested in a mode‐locked laser, it allows the generation of stable ≈326 fs mode‐locked pulses at 1550 nm, unperturbed by humidity and temperature. The composite continues to operate as a saturable absorber even under complete water immersion at 60 °C. This confirms its stability against high‐temperature and humidity.